"Monuments of German Baseness"? Confiscated Nazi war art and American occupation in the United States and postwar Germany. Issue 3 (August 2021) - Gramer, Jennifer
Abstract: Under the postwar American occupation of Germany, art produced by the Staffel der bildenden Künstler (German Combat Artist Unit) of Nazi Germany was sent to US military sites for storage under the direction of Captain Gordon Gilkey. Gilkey was head of the German War Art Project, the arm of the Historical Division of the US army tasked with confiscating German "propaganda and war art." This art, considered a dangerous instrument of Nazi revival, was not protected by laws prohibiting art looting. Yet American officers were sympathetic to many of the paintings created by combat artists, and the German combat artists themselves were torn about their roles in Nazism, perceiving themselves as either victims or survivors merely attempting to make a living. This article traces the history of this artwork from its seizure in postwar Germany through its internment in the United States up to later attempts in the 1950s and 1980s to restitute the works to their creators.